Evaluasi Atas Pelayanan Pendidikan Anak Berkebutuhan Khusus (ABK) Di Kabupaten bintan (Studi Di SMP Negeri 2 Bintan) - DIAH SITI UTARI; raja abumanshur matridi; Neng Suryanti Nengsih; Siti Rumduni (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Since 2021, SMP Negeri 2 Bintan has accepted students with special needs, although SMP Negeri 2 Bintan has not yet become a school with inclusive education. With inclusive education, it is hoped that it will become a strategy to equalize opportunities to obtain good educational services. The type of research used in this research is qualitative exploratory. Based on the research results, it can be seen that in order to provide good educational services at SMP Negeri 2 Bintan, there is still a lot that needs to be improved, starting from the acceptance of new students, the socio-economic conditions of parents of students with special needs, administrative requirements for inclusive teachers, facilities and infrastructure, program financing, competency of inclusive teachers, school exam results, social attitudes and evaluation finclusive education outcomes and those that have approached optimal educational services, namely the inclusive education curriculum, teachers' interest in teaching in inclusive classes, and the learning process ininclusive classes. Inconclusion, inefforts to accept students with special needs and payattention to inclusive education, there are still many aspects that need to be improved and improved.